Natural and Positive Law in the Concept of Correcting Offenders - Tatiana L. Shklyar3, Elena G. Bagreeva1, Alexander S. Blankov2, (Opción, 2019)
The aim of the study is to investigate natural and positive law inthe concept of correcting offenders via comparative qualitativeresearch methods. As a result, the actual task for the modern prisonsystems is not only serving the sentence in a safe environment, but alsoto help convicts to be ready for successful resocialization, asprevention of recurrence on the basis of norms of natural and positivelaw. In conclusion, implementation of the proposed penal concept ofcriminal reform will require, in practice, its deeper comprehension,understanding of the mechanisms and prerequisites of itsimplementation.